Physical testing and strength and conditioning practices differ between coaches working in academy and first team soccer - McQuilliam, S. J.; Clark, D. R.; Erskine, R. M.; Brownlee, T. E. (International Journal of Sports Science & Coaching, 2023)
Scientific guidelines exist regarding strength and conditioning (S&C) best practice, for both first team and academy level soccer. However, it is not known if these research-informed guidelines are followed in such applied settings. The aim of this study was to investigate current S&C practice in first team and academy level (men's and women's) soccer, in multiple countries/continents. A total of 170 participants, who were involved with the delivery of S&C support at their soccer club, completed a comprehensive survey, describing their training methods. Data were analysed using Pearson's chi-square test of independence and independent t-tests. Statistical significance was set to p < 0.05. A greater proportion of academy compared to first team coaches assessed acceleration/sprint (92% vs. 83%, p=0.026), jump (95% vs. 83%, p=0.023) and change of direction performance (77% vs. 61%, p=0.031). The weekly training structure differed between groups, particularly within women's squads, with women's academy coaches reporting the lowest session frequency of all groups (1.59 ± 0.62 session per week, 44 ± 17 min duration). A greater proportion of academy (54%) versus first team (35%) coaches prioritised bodyweight training (p=0.031), despite a similar distribution of movement patterns trained. Overall, 44% S&C coaches reported using training intensities below strength training guidelines (=80% 1RM). To conclude, there were many differences in S&C practice between S&C coaches working with first team and academy squads but particularly noteworthy was the greater proportion of academy coaches prioritising bodyweight training compared to first team coaches, which may limit physical development in academy players.